PENGEMBANGAN MODUL BERBASIS KONSTRUKTIVISME UNTUK MATERI KOMPOSISI FUNGSI DAN FUNGSI INVERS PADA PEMBELAJARAN MATEMATIKA SISWA KELAS XI IIS SMAN 8 PADANG - Asryesi, Silvia - (Pendidikan Matematika, 2014)
The background of the research is the studentâs difficulty on constructing the mathconcept of the materials about the function composition and invers function and lack ofthe material sources that are able to facilitate the students to study independently. Tosolve the problem, it is finally developed a constructivism-based module for the materialsof function composition and invers function. The research aims to know the validity andpractice of constructivism-based module in Public Senior High School 8 Padang. Thetype of the research is development. The research uses 4-D model that consists of 4stages, i.e. defining stage, designing stage, developing stage, and distributing stage. Theresearch is only conducted until the third stage, i.e. developing stage. The developingstage is conducted to know the validity and to test the practical module. The validity testresult of constructivism-based module of valid category is 4.07 for the average. Thestudents practical test result of very practical category is 93.03%. It can be concluded thatthe constructivism-based module on the materials of function composition and inversfunction is valid and practical.